Pemanfaatan Biji Nangka Sebagai Media Alternatif Untuk Pertumbuhan Bibit F0 Jamur Tiram Dan Jamur Merang - Rhaina Betharia, Nawangwulan, Dra. Suparti, M.Si (2017)
ABSTRACT Jackfruit seed is one grain that has 36.7% carbohydrate, 33% calcium, 42% protein, 0.1% fat, vitamin C 10 and 57.7% water, so it is able to suffice the nutritional needs of oyster mushroom mycelium growth and straw mushroom. This research was conducted to find out the growth of F0 oyster mushroom and straw mushroom by using jackfruit seeds as alternative media of potato substitute. The type of this research is qualitative descriptive with experimental research design. The research used experimentation research method with Complete Randomize Design (RAL) factorial pattern consisting of 6 treatments with 2 repetitions. Factor 1 was seedling of jackfruit extract media (M1), pulp media (M2), flour media (M3) and Factor 2 that is oyster mushroom (J1), straw mushroom (J2). Based on the result, the growth of mycelium on oyster mushroom and straw mushroom the growth alternative media jackfruit of seeds extract, pulp, and flour. Observation on day 3 and 7, the growth mycelium on day 3 is best at oyster mushroom in pulp media 6,75 cm and the longest at oyster extract media 1,25 cm. The growth mycelium on day 7 is best at straw mushroom in pulp media 9 cm and the longest at oyster mushroom in extract media 2,25 cm. The thickness of mycelium good first at of oyster mushrooms while the edible mushroom having a thin the mycelium. Keywords: mycelium growth, jackfruit seed, the media extract, pulp, flour.